2012
DOI: 10.1002/ijc.27851
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the RNA‐editing enzyme ADAR1 causes regression of established chronic myelogenous leukemia in mice

Abstract: Patients with chronic myelogenous leukemia (CML) respond well to tyrosine kinase inhibitors (TKIs) of the Bcr-Abl oncoprotein. However, intolerance and resistance to these agents remains a challenge, and TKI’s are unable to eradicate rare leukemia-initiating cells. Leukemia treatment would benefit from a better understanding of molecular signals that are necessary for the survival of leukemia-initiating cells but dispensable for normal hematopoietic stem cells. Leukemia-initiating cells in CML can arise from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
(99 reference statements)
0
30
0
Order By: Relevance
“…It has been demonstrated that ADAR1 is also involved in chronic myeloid leukemia. Indeed, Wang and collaborators reported that ADAR1 is required for Bcr-Abl leukemia cell survival in vivo and that silencing ADAR1 results in a rapid leukemic cell loss [63] . These studies elegantly uncover the role of ADAR1 in myeloid leukemia cells and indicate ADAR1 as a promising molecular target for CML-directed therapeutic interventions [63] .…”
Section: Heterogeneous Ribonuclear Proteins (Hnrnps)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that ADAR1 is also involved in chronic myeloid leukemia. Indeed, Wang and collaborators reported that ADAR1 is required for Bcr-Abl leukemia cell survival in vivo and that silencing ADAR1 results in a rapid leukemic cell loss [63] . These studies elegantly uncover the role of ADAR1 in myeloid leukemia cells and indicate ADAR1 as a promising molecular target for CML-directed therapeutic interventions [63] .…”
Section: Heterogeneous Ribonuclear Proteins (Hnrnps)mentioning
confidence: 99%
“…Indeed, Wang and collaborators reported that ADAR1 is required for Bcr-Abl leukemia cell survival in vivo and that silencing ADAR1 results in a rapid leukemic cell loss [63] . These studies elegantly uncover the role of ADAR1 in myeloid leukemia cells and indicate ADAR1 as a promising molecular target for CML-directed therapeutic interventions [63] . While ADAR1 seems to play a major role in disease affecting hematological compartment recently a role for the ADAR2 enzyme has also been recently demonstrated.…”
Section: Heterogeneous Ribonuclear Proteins (Hnrnps)mentioning
confidence: 99%
“…46,55 Hepatocytes free of nonparenchymal cells were isolated from the inducible ADAR1 KO mice by two-step liver perfusion, and the cells were cultured under 56,57 Tamoxifen was added to the culture medium to induce ADAR1 gene deletion ( Figure 6A). ADAR1 gene deletion was effectively achieved by tamoxifen induction in the hepatocytes, as verified by the PCR analysis of the ADAR1 gene alleles and diminishing levels of ADAR1 protein ( Figure 6, B and C).…”
Section: Adar1 In Liver Homeostasismentioning
confidence: 99%
“…55 Germline deletion of ADAR1 in mice results in embryonic lethality at embryonic 11.5 to 12 days after coitus. 28 Intriguingly, no obvious morphological defects are observed in organs other than the liver, including the placenta, heart, kidneys, brain, and other tissues, despite ADAR1 expression not being confined to the liver.…”
Section: Adar1 In Liver Homeostasismentioning
confidence: 99%
“…Due to the interferonresponsive ADAR1 activity, ADAR1 p150 was upregulated in chronic myeloid leukemia patient samples, which was correlated with BCR/ABL (oncogenic gene fusion protein) amplification and the increased A-to-I editing level [30]. Similarly, ADAR1 was also found to be required for the survival of leukemia cells [31]. Among different types of pediatric acute leukemias, only the B-cell acute lymphoblastic leukemia subgroup exhibited a significant overexpression of ADAR1 p110, with a dramatic decrease in its level in patients achieving complete remission [32].…”
Section: Adar1-regulated Rna Editing In Cancermentioning
confidence: 99%